Vascular Surgery Cases, Questions and Commentaries (Springer International Publishing, 2018)
The editors feel that to acknowledge new data and techniques in the area of vascular surgery there is a need for new chapters to be added to the book and for previous chapters to be updated. These changes will reassure the reader that the book is following the latest developments in the field of vascular and endovascular surgery and is still relevant, and therefore a useful companion in the practice of vascular surgery at the early stages of the career of vascular trainees and specialists. The new edition has been written along the principles of evidence based medicine and will be widely referenced, presenting vascular surgery through real life scenarios that are challenging the reader by asking questions.